ANALYSIS OF PHOTONIC BAND STRUCTURE IN PHOTONIC CRYSTALS CONTAINING SINGLE NEGATIVE MATERIALS BY COMPUTATION OF FIELD DISTRIBUTION AND DISPERSION DIAGRAMS - Vasudha Malhotra (International Journal of Research Science and Management, 2015)
A photonic crystal (PC) is said to be an artificially periodic layered structure that is known to possess photonic band gaps (PBGs) at certain frequency ranges. In this paper we have analysed one dimensional band structure by computational method in single negative material photonic crystals using plane wave expansion and finite difference time domain.